Emulation as a means to evaluate energy management algorithms = Emulacja jako środek do oceny algorytmów zarządzania energią - Turchan, Krzysztof; Piotrowski, Krzysztof; Krysik, Miłosz; Koropiecki, Igor; Powroźnik, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This article describes a Smart Grid Emulator. Its major goal is to demonstrate each block of the emulator as well as the simulator that supports it. It also shows the interdependencies between emulator and simulator. Using examples, it is described what test possibilities such an emulator provides.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne